Low level of antioxidant capacity biomarkers but not target overexpression predicts vulnerability to ROS-inducing drugs - Samarin, Jana; Fabrowski, Piotr; Kurilov, Roman; Nůsková, Hana; Hummel-Eisenbeiß, Johanna; Pink, Hannelore; Li, Nan; Weru, Vivienn; Alborzinia, Hamed; Yildiz, Umut; Grob, Laura; Täubert, Minerva Jazmin; et al. (Redox Biology, 2023)
Despite a strong rationale for why cancer cells are susceptible to redox-targeting drugs, such drugs often face tumor resistance or dose-limiting toxicity in preclinical and clinical studies. An important reason is the lack of specific biomarkers to better select susceptible cancer entities and stratify patients. Using a large panel of lung cancer cell lines, we identified a set of “antioxidant-capacity” biomarkers (ACB), which were tightly repressed, partly by STAT3 and STAT5A/B in sensitive cells, rendering them susceptible to multiple redox-targeting and ferroptosis-inducing drugs. Contrary to expectation, constitutively low ACB expression was not associated with an increased steady state level of reactive oxygen species (ROS) but a high level of nitric oxide, which is required to sustain high replication rates. Using ACBs, we identified cancer entities with a high percentage of patients with favorable ACB expression pattern, making it likely that more responders to ROS-inducing drugs could be stratified for clinical trials.
Gesehen am 01.02.2024